Framing Analysis in Online Media detik.com and tempo.co Related to Hydrometeorological Disasters - Aliifa, Dzikrifa Ningtyas; Putri, Winda Eka; Mirawati, Ira (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
As a country with high disaster risk, Indonesia faces the occurrence of hydrometeorological disasters such as floods, landslides, and strong winds that dominate more than 90% of disasters every year. In this situation, the media has a role in conveying information to the public. This study provides an overview of how news framing related to hydrometeorological disasters in two Indonesian online media, namely detik.com and tempo.co. Using a quantitative content analysis method, this study analyzes how detik.com and tempo.co framed the news related to hydrometeorological disasters from January 1, 2022, to November 1, 2024, with explores five main news frames from Semetko and Valkenburg. In addition, this study explores the tone of the news towards the government and the actors who become news sources. The results of the 85 articles analyzed show that the attribution of responsibility frame is the most dominant frame in the coverage of hydrometeorological disasters, followed by the frames of human interest, economy, and morality. In contrast, the conflict frame is very minimal. On the other hand, this study also found that the media mostly made the government the primary source of news and was also dominated by a neutral tone towards the government. This research found specific trends in using news frames, tone, and news sources in reporting hydrometeorological disasters. This research offers a perspective on how the media constructs narratives around hydrometeorological disasters while raising critical questions about the role of the press in shaping public understanding of climate-related disasters in Indonesia.